(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper delves into the portrayal of multiculturalism in Indian literature through the lens of media representation. Multiculturalism in India is not merely a socio-political construct but a deeply ingrained facet of its cultural landscape. Through an examination of literary works across various languages, genres, and historical periods, this research seeks to uncover the nuanced depictions of multiculturalism and their impact on societal perceptions and identities. By scrutinizing the role of media in shaping narratives of diversity, the study illuminates the complexities of multicultural coexistence in contemporary India. This exploration contributes to a deeper understanding of how literature, as mediated through various forms of media, reflects and shapes the multicultural ethos of Indian society.